Analisis Message Appeals Terhadap Purchase Intention Melalui Brand Awareness Sebagai Variabel Mediasi - Fany Mutia Rizki; Ramdan, Asep Muhamad; Norisanti, Nor (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the digital era, social media plays a very important role in selling beauty products. Displaying creative and innovative advertisements can increase purchase interest and improve the image of the product to be recognized by many people. This study aims to determine the effect of message appeals and brand awareness on purchase intention, as well as how the influence of brand awareness in mediating the relationship between message appeals and purchase intention in consumers of the originote products in the city of Sukabumi. This study uses quantitative research methods with a causal descriptive approach. The sampling technique in this study used probability sampling method, namely purposive random sampling with a total of 155 people in the city of Sukabumi who are interested in buying the originote skincare products. The data analysis technique used in this study is structural equation modeling (sem) using partial least square (pls). The results of this study indicate that there is a positive and significant effect of message appeals on brand awareness, a positive and significant effect of brand awareness on purchase intention and message appeals have a negative and insignificant effect on purchase intention on potential consumers of the originote product in the city of Sukabumi.